Long-Lasting Stable Expression of Human LL-37 Antimicrobial Peptide in Transgenic Barley Plants - Mirzaee, Malihe; Holásková, Edita; Mičúchová, Alžbeta; Kopečný, David J; Osmani, Zhila; Frébort, Ivo (Antibiotics (Basel), 2021)
Antimicrobial peptides play a crucial role in the innate immune system of multicellular organisms. LL-37 is the only known member of the human cathelicidin family. As well as possessing antibacterial properties, it is actively involved in various physiological responses in eukaryotic cells. Accordingly, there is considerable interest in large-scale, low-cost, and microbial endotoxin-free production of LL-37 recombinant peptides for pharmaceutical applications. As a heterologous expression biofactory, we have previously obtained homologous barley (Hordeum vulgare L.) as an attractive vehicle for producing recombinant human LL-37 in the grain storage compartment, endosperm. The long-term stability of expression and inheritance of transgenes is necessary for the successful commercialization of recombinant proteins. Here, we report the stable inheritance and expression of the LL-37 gene in barley after six generations, including two consecutive seasons of experimental field cultivation. The transgenic plants showed normal growth and remained fertile. Based on the bacteria viability test, the produced peptide LL-37 retained high antibacterial activity.